Morphological characteristics of a group of opossums (Didelphys marsupialis) in southwestern Colombia - Lozada, Santiago (2015)
Didelphidae family represents the majority of American marsupials distributed in South America. They are present in most type of habitats except in high mountains and deserts. They have different sizes and are described by some authors as medium and large size, while others indicate small and medium sizes. The present work contributes with a description ofDidelphys marsupialis located in the south west region of Colombia.